Changes in Alanine transaminase levels in response to statins: Sri Lankan experience in patient with type 2 Diabetes mellitus with Dyslipidemia - C.N. Antonypillai; W.C.K. Jayawardena; I.G. Samarakkody; S. Dahanayake; L. Monaragala; D.L.N. Wijerathne; T.L. Dassanayake (Sri Lanka Journal of Diabetes Endocrinology and Metabolism, 2018)
Background: Statins form the pharmacologic cornerstone of the primary and secondary prevention of atherosclerotic cardiovascular disease. While statins are well-tolerated by most people, the most common adverse effect is the asymptomatic elevation of serum aminotransferase levels. The objective of the study was to determine the incidence of changes in alanine transaminase (ALT) levels in patients who are on statin therapy and to identify cost effectiveness of monitoring of transaminases on a routine basis.   Methods: Wecarried out a retrospective cohort study in patients with Type 2 diabetes mellitus with dyslipidemia at the Diabetes and Endocrinology Unit, Teaching Hospital Kandy, Sri Lanka from August to October 2015. We measured the ALT levels before and after commencing statin therapy.   Results: This series comprised of 46 females and 24 males with a mean age of 58.2 years (SD =10.23). Mean total cholesterol, LDL, HDL, triglycerides were 229.94,153.10,46.63 and 146.34 mg/dL, respectively. The mean baseline ALT level was 32.86 U/L. Fifteen patients (21.42%) had baseline ALT levels above the upper limit of normal (>40U/L). Atorvastatin was the most commonly prescribed statin (98.57%). After a mean duration of 12.8 months of statin therapy, no patient had elevated ALT levels more than three times the upper limit of normal.  Only two patients (2.86%) had ALT levels greater than twice the upper limit of normal and they remained asymptomatic. Among the fifteen patients who had high baseline ALT, twelve (80%) had normal ALT following statin therapy.   Conclusions: Clinically significant increase in liver transaminases following statin therapy is rare. Hence, routine monitoring of transaminases levels may not be cost-effective.